AN ANALYSIS OF SPEECH ACT CLASSIFICATION IN BEAUTY AND THE BEAST - Diah Purwita Sintamutiani; Dias Fitriani; Ratih Inayah (IKIP Siliwangi, 2019)
Pragmatics is study of significance aspects and language use which are dependent to the speaker, the addressee and other characteristics about the context of utterance. Along with communication, we are as humans do it as speakers who deliver utterance or anything to the addressee. Therefore communication and language are related to another one with pragmatics. Usually people utilize language in spoken and written, for instance conversation writing ideas, thoughts and so on in the book. For example cerebration contained in fairy tale stories were poured through the writer that one may be understood by readers. These ideas are expressed in the form about speech acts as described in Yule's theory in his book Pragmatics: Speech Act Classification (1996), there are five classifications of speech act pragmatically that can be proposed with a speaker such as representatives, directives, commissives, expressives, and declarations. The researchers used Beauty and the Beast short story to be analyzed classification about speech act. The method used in this analysis is a descriptive qualitative method. The results in this study, there are 10 speech act in short story Beauty and the Beast. In the outcomes of this study, that speech act classified into 4 types. Speech act classification is mostly Directives (50%); Representatives (30%); Declarations (10%); and Commissives (10%). The classification type unfound in the story above is Expressives.